The History Boys: Critical reflections on our contributions to Management Learning and their ongoing implications. Issue 1 (February 2020) - Reynolds, Michael; Vince, Russ
In this reflective essay, written for the 50th anniversary of Management Learning, we look at the history of the journal from a unique vantage point, our interconnected, academic lived experience of publishing in the journal. Our aim is to undertake an historical review of our publications in Management Learning in order to identify the key themes of our work, to make connections with broader academic and social events of the time and to assert the continuing relevance of these themes for future scholarship. We review 27 papers that we have published in Management Learning since Volume 1 (1971) and identify four main themes from our papers. These are set in the context of the development of critical management education. We highlight the broader dimensions to our themes and suggest two areas with implications for future scholarship in Management Learning . In our conclusion, we use our findings and reflections to identify what we have learned about management learning, as well as making a call for action in relation to what we are labelling historical reflexivity.